2020
DOI: 10.30886/estima.v18.923_in
|View full text |Cite
|
Sign up to set email alerts
|

Development of educational material for the prevention and treatment of friction injuries

Abstract: Objective: to develop and validate an educational booklet to help health professionals to prevent and treat friction injuries. Method: methodological study. An integrative review of the literature of journals published between 2009 and 2019 was carried out in the main databases of Health Sciences. The evaluation of the educational booklet was conducted with 32 nurses, using the Delphi technique. The statistical analysis used was the Content Validity Index. Results: the judges considered the content of the educ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 24 publications
0
9
0
2
Order By: Relevance
“…Educational materials on skin lesions need to be based on scientific evidence (eg, articles with clinical relevance) that provides reliable information about technical, clinical, administrative, and financial procedures to improve care and reduce treatment costs. 22,23 This booklet was developed and structured after an integrative review of the literature and sent to the expert panel to be evaluated for effectiveness and functionality and validated using the Delphi technique. 10,13 The evaluators had the opportunity to comment on points they thought should be improved in the booklet content.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Educational materials on skin lesions need to be based on scientific evidence (eg, articles with clinical relevance) that provides reliable information about technical, clinical, administrative, and financial procedures to improve care and reduce treatment costs. 22,23 This booklet was developed and structured after an integrative review of the literature and sent to the expert panel to be evaluated for effectiveness and functionality and validated using the Delphi technique. 10,13 The evaluators had the opportunity to comment on points they thought should be improved in the booklet content.…”
Section: Discussionmentioning
confidence: 99%
“…12 The booklet was constructed based on the principles of development of booklets and protocols on healthcare. [8][9][10]13 The author observed in clinical practice that many health professionals had difficulty diagnosing, prescribing preventive measures, and treating patients with IAD or with risk factors for this condition. The study was conceived to address gaps in knowledge observed among healthcare professionals during daily clinical practice in long-term care facilities and primary healthcare services.…”
Section: Development Processmentioning
confidence: 99%
See 2 more Smart Citations
“…Por essa razão, é de extrema importância que o enfermeiro faça uma avaliação da pele do paciente no momento da sua admissão e identifique os fatores de risco que contribuem para o desenvolvimento das lesões por fricção. A partir disso, é necessário que sejam elaboradas estratégias voltadas para práticas de cuidados centradas na prevenção e tratamento das LF através de templates com base científica favorecendo a assistência de enfermagem (Salomé, 2020).…”
Section: Introductionunclassified